Clustering of District or City in Central Java Based COVID-19 Case Using K-Means Clustering - Ali Mahmudan (Jurnal Matematika, Statistika dan Komputasi, 2020)
Coronavirus Disease 2019 (COVID-19) is a new type of disease that has never been identified in humans. Severe cases of COVID-19 can cause acute respiratory syndrome, kidney failure, and even death. COVID-19 cases have spread all over the world, including in Indonesia. One province with a high number of COVID-19 cases is Central Java Province. Therefore, it is necessary to cluster districts or cities in Central Java based on the COVID-19 case to prevent the spread of COVID-19. Clustering the cases of COVID-19 is done using k-means clustering which is a method of clustering a number of data by means of partitions. The results show that cluster 2 and cluster 3 are areas that the government should pay more attention to because they are areas with a high number of active cases and the high death cases of COVID-19 in Central Java.